THE COURAGE TO SAY NO: THE PHILOSOPHER, THE DOG, AND THE DIGITAL NETWORK - Edstron Secundino Santos, Júlio (Revista Gênero e Interdisciplinaridade, 2026)
This research investigates Cynic philosophy, focusing on the figure of Diogenes of Sinope, proposing its theoretical and practical renewal as a fundamental critical tool in the contemporary era. The importance of this theme lies in the urgency of establishing mechanisms of psychological and social resistance in the face of the “Burnout Society” and digital hyperconnection, offering an indispensable ethical counterpoint to unbridled consumerism and the spectacularization of private life. To address this issue, the analysis adopts a methodology structured upon a triadic foundation: a comprehensive literature review of classical sources and modern commentators, an analysis of contemporary concrete cases (such as the Digital Detox and Zero Waste movements), and the rigorous application of the hypothetico-deductive method. The findings demonstrate that Cynicism transcends mere historical curiosity, revealing itself as a potent ontology of shock. The foundations of parrhesia (the courage of truth) and autarkeia (self-sufficiency) retain their full vitality as effective antidotes against contemporary pathologies. Ultimately, Cynic praxis operates as a veritable survival manual, proving that to inhabit the present with dignity requires askesis and the courage to say no to submission.